Firm Performance, Top Management Compensation, and Risk Preference: A Story of Indonesian Firms - Evy Rahman Utami; Indra Wijaya Kusuma (The Indonesian Journal of Accounting Research, 2019)
The issue of conflict of interests between shareholders and managers is interesting and widely examined. Compensation is often used to align the interests of managers with those of shareholders. This study aims, first, to show an empirical evidence of the relationship between company's performance and the manager’s compensation. In addition, this study also examines the impact of risk preference on that relationship. The sample for this study of manufacturing companies listed in the Indonesian Stock Exchange (BEI) for the period of 2008 to 2013. Data was obtained from annual reports, financial statements, and BvD Osiris. Regression analysis was employed to test the hypotheses. The results show that compensation is related more to accounting performance than to market performance. The compensation also had an impact on the future accounting performance, but not on future market performance. However, contrary to the expectation, risk preference does not strengthen the relationship between future compensation and future performance.  After splitting the sample into three categories, the compensation can motivate managers to increase the accounting performance only for companies with better performance.